High-Low Impact Exercise Program Including Pelvic Floor Muscle Exercises Improves Pelvic Floor Muscle Function in Healthy Pregnant Women – A Randomized Control Trial - Anna Szumilewicz; Marcin Dornowski; Magdalena Piernicka; Aneta Worska; Agnieszka Kuchta; Jakub Kortas; Monika Błudnicka; Łukasz Radzimiński; Zbigniew Jastrzębski (Frontiers in Physiology, 2019)
Background: Pregnancy and high-impact activity are considered as risk factors for pelvic floor dysfunctions, including urinary incontinence.Aim: To investigate whether a structured exercise program, including high- and low-impact aerobics and supported by pelvic floor muscle exercises, improves the neuromuscular activity of the pelvic floor and does not reduce the quality of life in terms of urinary incontinence in healthy pregnant women.Methods: This was a randomized control trial among 97 Caucasian healthy nulliparas in uncomplicated pregnancies (age 30 ± 4 years, 21 ± 5 weeks of gestation; mean ± SD). Women were assessed for pelvic floor muscle functions with surface electromyography (EMG) using vaginal probes and using the Incontinence Impact Questionnaire (IIQ). Only women able to contract pelvic floor muscles and with good quality of life based on IIQ were included for the study. Seventy women in the experimental group took part in a supervised exercise program including high-low impact aerobics and pelvic floor muscle exercises three times a week. Twenty-seven controls did not receive any exercise intervention. After 6 weeks both groups were re-tested with EMG and IIQ. Post- and pre-exercise program changes in each group were analyzed using a repeated-measures ANOVA.Results: Women in the experimental group improved the neuromuscular activity of the pelvic floor in some motor tasks without any adverse outcomes of the intervention. After the exercise program we observed in the experimental group significantly higher EMG amplitude in the pelvic floor muscles during 3-s contractions (p = 0.014). We also noticed a beneficial trend in the increase of neuromuscular activity during 10- and 60-s contractions, but the changes were not statistically significant. The exercising women substantially improved their abilities for relaxation following 3- and 10-s contractions (p = 0.013 and p < 0.001). In controls, we reported no statistically significant improvement in either of the motor tasks. All study participants maintained good quality of life related to urinary incontinence.Conclusion: Prenatal exercise programs that include high- and low-impact aerobics and are supported by pelvic floor muscle exercises should be recommended for pregnant women, especially those who are accustomed to higher exercise intensity before pregnancy. Nevertheless, these recommendations can be directed to continent women who can properly contract pelvic floor muscles.ISRCTN. DOI: 10.1186/ISRCTN92265528: “Pelvic floor muscle training with surface electromyography”, retrospectively registered on the 25th of July, 2016.